2018
DOI: 10.1002/1873-3468.13164
|View full text |Cite
|
Sign up to set email alerts
|

The type 1 transmembrane glycoprotein B7‐H3 interacts with the glycolytic enzyme ENO1 to promote malignancy and glycolysis in HeLa cells

Abstract: The role of the type 1 transmembrane glycoprotein B7-H3 is controversial in tumorigenesis; thus, a better clarification of its involvement in cancer is crucial. In the present study, 79.3% of cervical cancer samples were found to be B7-H3 positive and the expression of B7-H3 was positively correlated with the clinical features of the samples. Silencing B7-H3 using small interfering RNA or blocking it with intracellular ScFv attenuated the malignancy of HeLa cells. By pull-down assay and liquid chromatography-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Moreover, accelerated glycolysis increases the proliferation and invasion of non-small cell lung cancer 31 . Previous studies have demonstrated that the enhancement of aerobic glycolysis markedly promotes cancer cell growth and development 32,53,54 . However, studies focused on the association of glycolysis levels and stem-like characteristics of GC cells are scarce to nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accelerated glycolysis increases the proliferation and invasion of non-small cell lung cancer 31 . Previous studies have demonstrated that the enhancement of aerobic glycolysis markedly promotes cancer cell growth and development 32,53,54 . However, studies focused on the association of glycolysis levels and stem-like characteristics of GC cells are scarce to nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accelerated glycolysis increases the proliferation and invasion of non-small cell lung cancer [31]. Previous studies have demonstrated that enhancement of aerobic glycolysis markedly promotes cancer cells growth and development [32,53,54]. However, studies focused on the association of glycolysis levels and stem-like characteristics of GC cells are scarce to nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of ENO1 can promote tumor growth in hepatocellular carcinoma, and head and neck cancers, and functions as a potential oncogenic factor [29,30]. Furthermore, ENO1 was shown to in uence proliferation, metastasis and drug resistance in cancer cells by participating in the Warburg effect [31,32]. These studies indicated that ENO1 functioned as a potential oncogenic factor in endometrial carcinoma by inducing glycolysis [33].…”
Section: Read Full Licensementioning
confidence: 99%
“…Interestingly, hexokinase 1 and 2 (HK2) were also observed in both control and B7-H3 OE exosomes. A previous publication investigated the relationship between B7-H3 and ENO1, finding that downregulation of B7-H3 leads to a downregulation of ENO1 and subsequent impairment of glycolysis in HeLa cells [ 64 ]. Another study indicated that B7-H3 may promote glycolysis by upregulating HK2 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%